2013
DOI: 10.3109/15376516.2013.796032
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective role ofAbelmoschus esculentus(Linn.) Moench., on carbon tetrachloride-induced liver injury

Abstract: The results substantiated the hepatoprotective activity of A. esculentus through its antioxidant capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…For vegetables, it was shown that Abelmoschus esculentus Linn. extract improved cell viability and decreased the leakage of transaminases in HepG2 cells incubated with CCl 4 , and it could dose‐dependently increase the antioxidant levels, and reduce steatosis, necrosis, and inflammation in a rat model (Saravanan, Pandikumar, Pazhanivel, Paulraj, & Ignacimuthu, ). Besides, allyl isothiocyanate, an important component in radish, exhibited preventive effects on the liver, possibly by reducing lipid peroxidation, enhancing antioxidant enzymes, and suppressing Kupffer cells and macrophages (Ahn et al., ).…”
Section: Protective Effects Of Natural Products On Pollutant‐induced mentioning
confidence: 98%
“…For vegetables, it was shown that Abelmoschus esculentus Linn. extract improved cell viability and decreased the leakage of transaminases in HepG2 cells incubated with CCl 4 , and it could dose‐dependently increase the antioxidant levels, and reduce steatosis, necrosis, and inflammation in a rat model (Saravanan, Pandikumar, Pazhanivel, Paulraj, & Ignacimuthu, ). Besides, allyl isothiocyanate, an important component in radish, exhibited preventive effects on the liver, possibly by reducing lipid peroxidation, enhancing antioxidant enzymes, and suppressing Kupffer cells and macrophages (Ahn et al., ).…”
Section: Protective Effects Of Natural Products On Pollutant‐induced mentioning
confidence: 98%
“…The ability of okra extract to protect chemically induced liver damage may be attributed to its potent antioxidant property. Subramanian Saravanan et al, also found in "Hepatoprotective role of Abelmoschus esculentus on carbon tetrachloride-induced liver injury," that the incubation of human liver cancer cell line with CCl₄ decreased the cell viability and increased the leakage of transaminases and Pre-treatment with the extract significantly restored the cell death and reduced the levels of transaminases 34 .…”
Section: Fig 9: Represent the Mean Difference Of Alkaline Phosphtasementioning
confidence: 99%
“…Since liver is mainly responsible for metabolizing ingested alcohol; therefore it is more susceptible to alcohol related injury [32] . Chronic alcohol con- stress in liver disease related to chronic alcohol consumption [33,34] .…”
Section: Chemicals Induced Hepatotoxicity 41 Alcoholmentioning
confidence: 99%